1996
DOI: 10.1136/jmg.33.5.435
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of GLRA1 in hereditary and sporadic hyperekplexia: a novel mutation in a family cosegregating for hyperekplexia and spastic paraparesis.

Abstract: Hyperekplexia is a rare condition characterised by the presence of neonatal hypertonia and an exaggerated startle response. Mutations have been described in GLRA1, the gene encoding the al subunit of the glycine receptor, in dominant families with hyperekplexia and in a single sporadic case, thought to represent an autosomal recessive form of the disease.In this study the coding region of the GLRA1 was analysed in eight probands with hyperekplexia by restriction digest and sequencing. Two familial cases were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 9 publications
2
52
0
1
Order By: Relevance
“…In glycine receptors, mutations in the M2-M3 loop can strongly inhibit channel activation, and thus cause hyperekplexia (Langosch et al, 1994;Chung et al, 2010). Our early work (Lewis et al, 1998) showed that one such hyperekplexia mutation in position 24Ј, ␣1K276E (Elmslie et al, 1996), acts by impairing gating.…”
Section: Introductionmentioning
confidence: 99%
“…In glycine receptors, mutations in the M2-M3 loop can strongly inhibit channel activation, and thus cause hyperekplexia (Langosch et al, 1994;Chung et al, 2010). Our early work (Lewis et al, 1998) showed that one such hyperekplexia mutation in position 24Ј, ␣1K276E (Elmslie et al, 1996), acts by impairing gating.…”
Section: Introductionmentioning
confidence: 99%
“…13 Mutations in the GLRA1 gene on chromosome 5, which codes for the alpha 1 subunit of the glycine receptor have previously been described for hyperekplexia when it occurs in isolation and also when the hyperekplexia occurs with spastic paraparesis. 14 A locus in the paracentric region of chromosome 8 was linked to 'pure' AR HSP in four out of five Tunisian families examined 15 providing evidence for genetic heterogeneity in autosomal recessive HSP. Linkage of 'pure' and 'complicated' families to the SPG1 (Xq21-22) and SPG2 (Xq28) loci on the X chromosome confirms the existence of genetic heterogeneity for X-linked HSP.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the startle mutations R271L/Q and K276E map to the M2-M3 linker domain (5,7). At both locations, the mutations result in the substitution of a positive charged residue.…”
mentioning
confidence: 99%